TREND OF INCIDENCE FOR ENTEROBIASIS IN MONTENEGRO IN THE PERIOD 2010-2019 - Bojanic, Jelena; Grujicic, Sandra (HEALTH CARE, 2021)
Introduction / Aim: It is estimated that more than one billion people worldwide suffer from enterobiasis each year. Enterobiasis is the most common helminthiasis in developed countries such as northwestern Europe and North America. The aim of this descriptive study is to analyze the trends in enterobiasis in the Republic of Montenegro for the period from 2010 to 2019. Methods: Data on enterobiasis were taken from the Annual Report on Infectious Diseases in Montenegro, the Institute of Public Health of Montenegro. Data on the number of inhabitants of Montenegro for 2011 were taken from the census, and for other years the estimated number of inhabitants from the publications of the Republic Statistical Office was used. Crude, age-specific and standardized incidence rates were applied in the data analysis. Results: In the period from 2010 to 2019, 1308 people with enterobiasis were reported in Montenegro. The ratio of affected men and women was 1: 1.3. No deaths from this disease have been reported. The highest crude incidence rates for both sexes are in the 0-4 age group and are 172.9/100,000 for men and 175/100,000 for women. The average annual crude incidence rate of enterobiasis for this ten-year period was 21.1/100,000 inhabitants (21.1/100,000 for women and 21.0/100,000 for men), and the standardized (according to the population of Europe) 29.3/100,000 (30.7/100,000 for women and 27.9 /100,000 for men). The trend of crude incidence rates shows a slight upward trend, but without statistical significance. Conclusion: Hand hygiene is the best measure to prevent enterobiasis. In households where more than one member is infected or symptomatic infections recur, it is recommended that all household members should be treated at the same time, regardless of whether they have symptoms or not. It is necessary to repeat the treatment in two weeks, because antihelmintics act only on adult parasites, and not on eggs / larvae from which new individuals develop.